The FICI grading for a dacryocystorhinostomy ostium. Issue 1 (January 2022) - Ali, Mohammad Javed; Gupta, Adit; Lakshmi, Chittabhathina Sri; Ali, Mohammad Hasnat
Purpose: The objective of this study is to propose a simple grading to assess the health of a dacryocystorhinostomy (DCR) ostium. Methods: Prospective case series of 237 Ostia evaluated following dacryocystorhinostomy were included in the study. All the ostia were assessed for 10 parameters in detail using the earlier published DCR ostium scoring (DOS scoring). Each of the 10 parameters were scored individually, and final DOS scores were obtained. The anatomical and functional outcomes of each of the surgery were noted. The most significant parameters that influenced the success were determined using the binary recursive partitioning in a conditional inference framework. Data management and statistical tests were performed using the statistical "Software R" and the library "partykit" toolkits. Results: The most significant DCR ostium parameters that influenced the outcomes were anatomical and functional fluorescein dye transit ( p  < 0.001), dynamicity of internal common opening (ICO) on the blink ( p  < 0.001), end-on threats to ICO from granuloma, membrane or a synechia, and cicatricial closure of the Ostia. Each of these significant factors (FICI – Fluorescein endoscopy dye test, ICO dynamicity, Cicatricial ostium closure and ICO threats) were assigned simple scoring and the final scores were graded from 0 (poor DCR ostium) to +5 (excellent DCR ostium). FICI grading can guide the physician on the health status of the DCR ostium and the possible need for intervention. Conclusion: FICI DCR ostium grading is a simple, easy to perform, and physician-friendly system. More studies with larger sample size would help in further validating the FICI grading.